Are vectors able to learn about their hosts? A case study with Aedes aegypti mosquitoes - Wladimir J Alonso; Tristram D Wyatt; David W Kelly (Memorias do Instituto Oswaldo Cruz, 2003)
The way in which vectors distribute themselves amongst their hosts has important epidemiological consequences. While the role played by active host choice is largely unquestioned, current knowledge relates mostly to the innate response of vectors towards stimuli signalling the presence or quality of their hosts. Many of those cues, however, can be unpredictable, and therefore prevent the incorporation of the appropriate response into the vector's behavioural repertoire unless some sort of associative learning is possible. We performed a wide range of laboratory experiments to test the learning abilities of the mosquito, Aedes aegypti. Mosquitoes were exposed to choice procedures in (1) an olfactomenter and (2) a 'visual arena'. Our goal was to determine whether the mosquitoes were able to associate unconditional stimuli (blood feeding, human breath, vibration and electrical shock) with particular odours (citral, carvone, citronella oil and eugenol) and visual patterns (horizontal or vertical black bars) to which they had been previously observed to be responsive. We found no evidence supporting the hypothesis that associative learning abilities are present in adult Ae. aegypti. We discuss the possibilities that the assays employed were either inappropriate or insufficient to detect associative learning, or that associative learning is not possible in this species.